Biogeochemistry of Cyclic Microelements in Hydromorphic Soils (Texas Journal of Agriculture and Biological Sciences, 2023)
The work, based on its own and literary sources, presents materials on the content of iron, aluminium, silicon and other cyclic chemical elements in irrigated meadow saz soils with аrzyk-shokho metamorphic horizons of Central Fergana. It has been established that Fe, Al, Si and other cyclic elements accumulate at these horizons.